PTH-128 The weekend effect: the impact of out-of-hours liver transplantation upon transplant survival. (22nd June 2015) - Halliday, N; Martin, K; Allen, E; Thorburn, D
Abstract : Introduction: There is an excess mortality associated with weekend medical admissions for many conditions and poorer surgical outcomes with night-time (NT) operating. Due to the time critical nature of organ retrieval for liver transplantation many transplants occur 'out-of-hours'. We sought to identify if there was an impact upon transplant survival (a composite outcome of graft failure or death) with weekend (5pm Friday to 8am Monday) or NT (7 pm to 7 am) liver transplantation. Method: Data on 8338 liver only transplants were obtained from the UK Transplant Registry, as at 04/01/2015. These included only those with adult NHS group 1 recipients (aged 17 or more) transplanted in the UK from solid organ deceased donors from 1 January 2000 to 31 December 2014. Cox proportional hazard models were created controlling for variables with a statistical impact on survival such as renal support, ventilation status, sepsis, graft appearance, CIT, donor type, split liver and transplant year. Results: There was a significant reduction in the hazard of the composite outcome of graft failure or death at 30 days (adjusted hazard ratio: 0.79, 95% CI: 0.67–0.93, p-value: 0.01), 90 days (0.83, 0.72–0.95, 0.01), 1 year (0.87, 0.77–0.97, 0.02) and 3 years (0.89, 0.80–0.99, 0.03) associated with weekend transplantation but not with NT transplantation. However, when the analysis was conditioned to only those patients alive and with a functioning graft at 30 days post transplantation, the weekend effect was no longer significant at both 1 year (0.96, 0.81–1.133, 0.62) and 3 years (0.96, 0.85–1.10, 0.59). Conclusion: We have demonstrated a significant reduction in death or graft failure associated with liver transplantation at weekends of 10–20%, which is pertinent only to the early post-operative transplant survival. American studies have shown no change in outcomes with weekend liver transplantation but a possible increase in early mortality with nighttime operating in one small study. The reasons for reduced adverse outcomes with weekend transplantation are unclear. It may represent a "lead-in" effect as patients transplanted at the weekend will be in intensive care for the first days following surgery, where service provision is similar 7 days a week, and step down to level one care during the week rather than at weekends. Other factors may include transplanting teams being risk adverse at weekends and more likely to decline marginal organs for grafting and prioritising less complex cases for weekend working. This is a novel and interesting finding that requires deeper analysis of the data set and prospective monitoring. Disclosure of interest: None Declared.